2016
DOI: 10.1002/adfm.201602652
|View full text |Cite
|
Sign up to set email alerts
|

Understanding of the Extremely Low Thermal Conductivity in High‐Performance Polycrystalline SnSe through Potassium Doping

Abstract: P‐type polycrystalline SnSe and K0.01Sn0.99Se are prepared by combining mechanical alloying (MA) and spark plasma sintering (SPS). The highest ZT of ≈0.65 is obtained at 773 K for undoped SnSe by optimizing the MA time. To enhance the electrical transport properties of SnSe, K is selected as an effective dopant. It is found that the maximal power factor can be enhanced significantly from ≈280 μW m−1 K−2 for undoped SnSe to ≈350 μW m−1 K−2 for K‐doped SnSe. It is also observed that the thermal conductivity of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

11
174
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 210 publications
(185 citation statements)
references
References 52 publications
11
174
0
Order By: Relevance
“…[14] The above examples clearly illustrate that SnSe polycrystals could be engineered into promising thermoelectric materials by diverse approaches, such as n-type and p-type doping, [12,[14][15][16][17] alloying, [13,14,16] nanostructuring [11,13] and microstructure modulation. [14] The above examples clearly illustrate that SnSe polycrystals could be engineered into promising thermoelectric materials by diverse approaches, such as n-type and p-type doping, [12,[14][15][16][17] alloying, [13,14,16] nanostructuring [11,13] and microstructure modulation.…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations
“…[14] The above examples clearly illustrate that SnSe polycrystals could be engineered into promising thermoelectric materials by diverse approaches, such as n-type and p-type doping, [12,[14][15][16][17] alloying, [13,14,16] nanostructuring [11,13] and microstructure modulation. [14] The above examples clearly illustrate that SnSe polycrystals could be engineered into promising thermoelectric materials by diverse approaches, such as n-type and p-type doping, [12,[14][15][16][17] alloying, [13,14,16] nanostructuring [11,13] and microstructure modulation.…”
Section: Introductionmentioning
confidence: 98%
“…[1,7] Recently, SnSe single crystals have produced a surge in the field of thermoelectrics as a new type of promising TE materials because of the intrinsically ultralow thermal conductivity (<0.4 W m −1 K −1 at 923 K) and high ZT along the b-and c-crystallographic directions (>2.3 at 923 K). [10][11][12][13][14][15] For example, Wei et al [12] reported a ZT of ≈0.8 at 800 K in 1% Na-and K-doped SnSe, which was produced by conventional solid state reaction followed by a spark plasma sintering (SPS) treatment. [9] Nevertheless, the difficulties in large-scale synthesis of single crystals limit their practical applications, and extensive efforts have been devoted to the fabrication of high-performance polycrystalline counterparts.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…21,23 The measured j lat values have also been reported to be sensitive to oxidation. 24 However, the promise of SnSe as an outstanding thermoelectric material is not in doubt as Na-doped single crystals show greatly improved thermoelectric power factors near room temperature and compete with the best known Bi 2 Te 3 based alloys in terms of their efficiency. 25,26 In this Letter, we report an investigation into the lowtemperature heat capacity of SnSe and combine this with crystal structure data to yield important insights into the thermal behaviour of SnSe.…”
mentioning
confidence: 99%
“…The electrical conductivities of skutterudite and half-Heusler, both well-known intermediate-temperature thermoelectric materials, are above 1000 S/cm in overall temperature ranges [1,14]. The electrical conductivity of SnSe is only 18.1 S/cm, indicating that it is not necessary to have low SCR as in other materials [15]. As a result, several 10 −3 Ω·cm 2 SCR of SnSe thermoelectric material could be approximated to be the same as the 10 −4~1 0 −5 Ω·cm 2 SCR of skutterudite and half-Heusler thermoelectric materials.…”
Section: Resultsmentioning
confidence: 99%